Dendrosomal nanocurcumin promotes remyelination through induction of oligodendrogenesis in experimental demyelination animal model. (18th August 2020) - Motavaf, Mahsa; Sadeghizadeh, Majid; Babashah, Sadegh; Zare, Leila; Javan, Mohammad
Abstract: Multiple sclerosis (MS) is an autoimmune disease, associated with central nervous system (CNS) inflammation, demyelination, and axonal loss. Myelin, a multilayer membranous that covers nerve fibers, is essential for rapid impulse conduction. Oligodendrocytes that are generated either from CNS‐resident oligodendrocyte progenitor cells (OPCs) or subventricular zone‐derived neural stem cells (NSCs) are the myelinating cells of the CNS. The adult CNS maintains a certain endogenous potential to repair myelin damage. However, this process often fails as MS progresses. The origin of this failure is not fully understood, but it is likely to relate to progenitors/stem cells' arrestment in a quiescent state, incapable of generating new oligodendrocyte. Current treatments for MS are immunomodulatory or immunosuppressive medications, with little to no effect on myelin restoration. Recent studies have provided proof‐of‐principle that CNS remyelination can be promoted either via enhancing endogenous remyelination or by transplanting myelinating cells. Curcumin, a natural polyphenolic compound, has been shown to have therapeutic properties in several neurodegenerative diseases. Here, we investigated the effect of a curcumin nanoformulation, dendrosomal nanoparticles (DNC) on oligodendrogenesis and remyelination, both in vitro and in animal model of demyelination. We indicated that DNC enhanced oligodendrogenesis from NSCs and OPCs, in vitro in dose dependent manner. DNC also induced in vivo remyelination via promotion of oligodendrogenesis. Furthermore, DNC enhanced remyelination capacity of transplanted NSCs through promoting their survival and oligodendrogenesis capacity. Our findings suggest that DNC has significant beneficial effects in demyelinating conditions, either as mono‐therapy or as being paired with transplantation approaches.